Filmer l’artificialisation d’une terre agricole périurbaine - Olivier Bories (Projets de Paysage)
The article presents ongoing research on the urbanisation of peri-urban agricultural land due to a real estate project. It focuses on the transformation of the landscapes of the urban fringes and on the interactions between the stakeholders implementing the project. The field of research is in the agglomeration of Toulouse, and more specifically the small municipality of Vigoulet-Auzil situated to the south of the city. So far “miraculously” preserved from urbanisation, the municipality is now conducting urban planning with the aim of revitalising the area. A film camera and microphone are used to capture the impacts of the changes. The objective is to produce a research film documenting the study which uses images and sounds to produce a different type of scientific document. These images and sounds are used to collect the data and to produce and report the findings. The article focuses on the project, on the initial research findings, and above all on the filming method used to record and report these findings.